Sports Safety: Analysis of Injury Trends and Sports Injury Prevention Strategies - Arfan Julistya Hadi; Irvan Septianto; Fadel Muhammad; Zaniar Dwi Prihatin Ciptadi; Andi Muh Ridwan Anwar (Universitas Cahaya Prima, 2025)
Sport has many benefits for physical, mental and social health. However, athletes, coaches and medical staff face significant challenges regarding the risk of sports injuries. This article analyzes trends in sports injuries, investigates the factors that cause them, and discusses effective prevention strategies. Trend analysis shows that in the 15 to 25 year old age group in Finland, there is an increase in injuries, as well as differences between genders. Injuries related to sports such as soccer and basketball are increasing in the United States. Studies in Europe show that hamstring injuries are increasing during matches. Injuries can be caused by inappropriate equipment, overtraining, and insufficient warm-up. This review is based on literature published between 2015–2024, collected from Google Scholar, PubMed, and ScienceDirect, focusing on sports injury trends, causal factors, and prevention strategies. Key findings highlight the effectiveness of programs such as PEP and FIFA 11+, the importance of neuromuscular training, and athlete-centered safety planning. Future sports safety policies should integrate evidence-based prevention frameworks to ensure safer and more sustainable sports participation. The purpose of this article is to analyze current injury trends, the factors that influence them, and find out strategies to reduce the risk of injury in this dynamic world of sports.